Applications of Subleading-Color Amplitudes in N=4 SYM Theory - Naculich, Stephen G.; Nastase, Horatiu [UNESP]; Schnitzer, Howard J. (Hindawi Publishing Corporation, 2011)
A number of features and applications of subleading-color amplitudes of N = 4 SYM theory are reviewed. Particular attention is given to the IR divergences of the subleading-color amplitudes, the relationships of N = 4 SYM theory to N = 8 supergravity, and to geometric interpretations of one-loop subleading- color and NkMHV amplitudes of N = 4 SYM theory.